2020
DOI: 10.1021/acs.inorgchem.0c02232
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Copper Sulfide Formation from Cu and S K edge XAS and DFT studies

Abstract: An understanding of the fundamentals of the reaction between CuO with trace amounts of H 2 S to form CuS products is critical for the optimal utilization of this process in sulfur removal applications. Unfortunately, CuS is a complex material, featuring various Cu 2-x S compounds (with 0 ≤ x ≤ 1), distorted crystal phases, and varying electronic structures and coordination environments of Cu and S ions. In this work, we combine ex situ and in situ X-ray absorption spectroscopy (XAS) at S and Cu K edges, fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…The phase and strain identification from XRD analysis support the conclusion of La incorporation into CuO. As mentioned above, the La-containing samples exhibit higher removal capacities than the CuO sample despite possessing larger CuO crystallites, and according to previous work (both by the authors 23,25 and others 22 ), the increase in capacity results from strain induced by lattice expansion. Thus, the addition of La into CuO disrupts the lattice and leads to the increase in H 2 S capacity.…”
Section: Phyiscochemical Properties Of La-cuo Sorbents Identified Via Nonsynchrotron Based Techniquessupporting
confidence: 73%
See 4 more Smart Citations
“…The phase and strain identification from XRD analysis support the conclusion of La incorporation into CuO. As mentioned above, the La-containing samples exhibit higher removal capacities than the CuO sample despite possessing larger CuO crystallites, and according to previous work (both by the authors 23,25 and others 22 ), the increase in capacity results from strain induced by lattice expansion. Thus, the addition of La into CuO disrupts the lattice and leads to the increase in H 2 S capacity.…”
Section: Phyiscochemical Properties Of La-cuo Sorbents Identified Via Nonsynchrotron Based Techniquessupporting
confidence: 73%
“…In summary, the laboratory‐based characterization showed that CuO‐La‐2, compared to CuO‐La‐1, features larger crystals but has a higher inclusion of La throughout the CuO phase. These results suggest that the improvement in sulfur uptake by CuO‐La‐2, compared to CuO‐La‐1, is related to a higher concentration of La dopants which induce lattice expansion and strain, which have been previously identified as a means to increase H 2 S capacity of CuO adsorbents 22,23,25 …”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations